Stercurensin Inhibits Nuclear Factor-kappa B-Dependent Inflammatory Signals Through Attenuation of TAK1-TAB1 Complex Formation - Kim, Young-Joo; Kim, Han-Cheon; Ko, Hyeonseok; Amor, Evangeline C.; Lee, Jong Wha; Yang, Hyun Ok (WILEY, 2011)
We identified a chalcone, 2',4'-dihydroxy-6'-methoxy-3'-methylchalcone (stercurensin), as an active compound isolated from the leaves of Syzygium samarangense. In the present study, the anti-inflammatory effects and underlying mechanisms of stercurensin were examined using lipopolysaccharide (LPS)-stimulated RAW264.7 cells and mice. To determine the effects of stercurensin in vitro, inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) expression were analyzed by RT-PCR and immunoblotting. Nuclear factor-kappa B (NF-kappa B) activation and its upstream signaling cascades were also investigated using a dual-luciferase reporter assay, electrophoretic mobility shift assay, immunoblotting, immunofluorescence, and immunoprecipitation. To verify the effects of stercurensin in vivo, the mRNA expression levels of iNOS and COX-2 were evaluated in isolated mouse peritoneal macrophages by quantitative real-time PCR, and the production of tumor necrosis factor-alpha (TNF-alpha), interleukin-6 (IL-6), and IL-1 beta were assessed in serum samples from mice using a Luminex system. Pretreatment with stercurensin reduced LPS-induced iNOS and COX-2 expression, thereby inhibiting nitric oxide (NO) and prostaglandin E-2 production, respectively. In addition, an inhibitory effect of stercurensin on NF-kappa B activation was shown by the recovery of LPS-induced inhibitor of kappa B (1-kappa B) degradation after blocking the transforming growth factor-beta-activated kinase 1 (TAK1)/I-kappa B kinase signaling pathway. In mouse models, stercurensin negatively regulated NF-kappa B-dependent pro-inflammatory mediators and cytokines. These results demonstrate that stercurensin modulates NF-kappa B-dependent inflammatory pathways through the attenuation of TAK1-TAB1 complex formation. Our findings demonstrating the anti-inflammatory effects of stercurensin in vitro and in vivo will aid in understanding the pharmacology and mode of action of stercurensin. J Cell. Biochem. 112: 548-558, 2011. (C) 2010 Wiley-Liss, Inc.
Keywords: ACTIVATED PROTEIN-KINASE; NITRIC-OXIDE SYNTHASE; INDUCIBLE CYCLOOXYGENASE; MEDIATED ACTIVATION; DOWN-REGULATION; TAK1; SUPPRESSION; EXPRESSION; FLAVONOIDS; PATHWAYS